A comprehensive exploration of artificial intelligence in orthopaedics within lower-middle-income countries: a narrative review - Umm E Salma Shabbar Banatwala; Muhammad Talal Ibrahim; Reyan Hussain Shaikh; Hania Shahzad; Zahra Hoodbhoy; Shahryar Noordin (Journal of the Pakistan Medical Association, 2024)
Integrating Artificial Intelligence (AI) in orthopaedic within lower-middle-income countries (LMICs) promises landmark improvement in patient care. Delving into specific use cases—fracture detection, spine imaging, bone tumour classification, and joint surgery optimisation—the review illuminates the areas where AI can significantly enhance orthopaedic practices. AI could play a pivotal role in improving diagnoses, enabling early detection, and ultimately enhancing patient outcomes— crucial in regions with constrained healthcare services. Challenges to the integration of AI include financial constraints, shortage of skilled professionals, data limitations, and cultural and ethical considerations. Emphasising AI’s collaborative role, it can act as a complementary tool working in tandem with physicians, aiming to address gaps in healthcare access and education. We need continued research and a conscientious approach, envisioning AI as a catalyst for equitable, efficient, and accessible orthopaedic healthcare for patients in LMICs. Keywords: Artificial Intelligence, Orthopaedics, Health Services, Patient Care, Bone Neoplasms, Physicians, precision medicine; predictive analysis